The Abelson tyrosine kinase, the Trio GEF and Enabled interact with the Netrin receptor Frazzled in Drosophila. - Forsthoefel, D.J.; Liebl, E.C.; Kolodziej, P.A.; Seeger, M.A. (Development, 2005)
The attractive Netrin receptor Frazzled (Fra), and the signaling molecules Abelson tyrosine kinase (Abl), the guanine nucleotide-exchange factor Trio, and the Abl substrate Enabled (Ena), all regulate axon pathfinding at the Drosophila embryonic CNS midline. We detect genetic and/or physical interactions between Fra and these effector molecules that suggest that they act in concert to guide axons across the midline. Mutations in Abl and trio dominantly enhance fra and Netrin mutant CNS phenotypes, and fra;Abl and fra;trio double mutants display a dramatic loss of axons in a majority of commissures. Conversely, heterozygosity for ena reduces the severity of the CNS phenotype in fra, Netrin and trio,Abl mutants. Consistent with an in vivo role for these molecules as effectors of Fra signaling, heterozygosity for Abl, trio or ena reduces the number of axons that inappropriately cross the midline in embryos expressing the chimeric Robo-Fra receptor. Fra interacts physically with Abl and Trio in GST-pulldown assays and in co-immunoprecipitation experiments. In addition, tyrosine phosphorylation of Trio and Fra is elevated in S2 cells when Abl levels are increased. Together, these data suggest that Abl, Trio, Ena and Fra are integrated into a complex signaling network that regulates axon guidance at the CNS midline.